PELATIHAN ISLAMIC FINANCIAL PLANNING FOR TEACHER SEBAGAI UPAYA PENINGKATAN LITERASI KEUANGAN SYARIAH GURU DAN TENAGA PENDIDIK DI INDONESIA - Putri Syifa Amalia (Tazkia Islamic University College, 2026)
Teachers and educators play a strategic role in shaping the financial mindset and behavior of the younger generation. However, based on OJK’s 2022 National Survey on Financial Literacy and Inclusion (SNLIK), the Islamic financial literacy index in Indonesia stands at only 9.14%, including among educators. This community service activity aims to enhance teachers’ and educators’ understanding of Islamic-based financial planning through the Islamic Financial Planning for Teacher training program. The activity was conducted online via Zoom Meeting on December 21, 2024 / 19 Jumadil Akhir 1446 H, from 08.30 to 11.30 WIB, with fewer than 30 participants who are teachers and educators from various provinces across Indonesia. Training materials covered the basic concepts of Islamic financial planning, halal cash flow management, Islamic investment planning, and financial protection through takaful. Evaluation results showed an improvement in participants’ understanding of Islamic financial planning concepts, reflected in positive feedback responses from participants. Participants received an e-certificate equivalent to 2 SKP, worksheets, training recordings, and material modules as tools for implementation in their respective school environments. This activity is expected to create a multiplier effect in increasing Islamic financial literacy through the strategic role of teachers as agents of change.